30 Years of postdisturbance recruitment in a Neotropical forest. Issue 21 (7th October 2021) - Mirabel, Ariane; Marcon, Eric; Hérault, Bruno
Abstract: Questions: Long‐term community response to disturbance can follow manifold successional pathways depending on the interplay between various recruitment processes. Analyzing the succession of recruited communities provides a long‐term perspective on forest response to disturbance. Specifically, postdisturbance recruitment trajectories assess (a) the successive phases of postdisturbance response and the role of deterministic recruitment processes, and (b) the return to predisturbance state of recruits taxonomic/functional diversity/composition. Location: Amazonian rainforest, Paracou station, French Guiana. Methods: We analyzed trajectories of recruited tree communities, from twelve forest plots of 6.25 ha each, during 30 years following a disturbance gradient that ranged from 10% to 60% of aboveground biomass removed. We measured recruited community taxonomic composition turnover, compared to whole predisturbance community, and assessed their functional composition by measuring the community weighted means for seven leaf, stem, and life‐history functional traits. We also measured recruited community taxonomic richness, taxonomic evenness, and functional diversity and compared them to the diversity values from a random recruitment process. Results: While control plots trajectories resembled random recruitment trajectories, postdisturbance trajectories diverged significantly. This divergence corresponded to an enhanced recruitment of light‐demanding species that became dominant above a disturbance intensity threshold. After breakpoints in time, though, recruitment trajectories returned to diversity values and composition similar to those of predisturbance and control plots community. Conclusions: Following disturbance, recruitment processes specific to undisturbed community were first replaced by the emergence of more restricted, deterministic recruitment processes favoring species with efficient light use and acquisition. Then, a second phase corresponded to a decades‐long recovery of recruits predisturbance taxonomic and functional diversity and composition that remained unachieved after 30 years. Abstract : We examined recruited trees taxonomic/functional diversity/composition trajectories in a Neotropical forest to identify the processes underlying community response to a disturbance gradient. We revealed a two‐phase successional pathway defined by (a) the emergence of deterministic recruitment processes enhancing the recruitment of light‐demanding species and (b) a decades‐long recovery towards the pre‐disturbance composition and diversity values.